Judas or Jesus’ Other Disciples? The Old Testament or Jesus’ Word? A Mysterious Reference to the “Scripture” in John 17:12 - Kubiś, Adam (The Biblical Annals, 2019)
The fulfillment of “the Scriptures” in John 17:12 has long been a bone of contention among commentators on the Fourth Gospel. The majority of authors have argued that ἡ γραφή unmistakably refers to a passage in the Hebrew Bible. Wendy Sproston (North) and Francis Moloney, however, picking up on an earlier observation by Edwin Freed, suggest Jesus’ own words as a more appropriate referent of ἡ γραφή in this verse. The issue of the correct scriptural referent is intrinsically connected with the question of the thematic referent within the verse in question. As it turns out, the fulfillment of the scripture can refer to either the tragic fate of Judas or the preserving of Jesus’ other disciples. The article surveys recent scholarship on these issues in order to identify the most convincing solutions.